Electrocardiographic pathological findings caused by the SARS-CoV-2 virus infection: evidence from a retrospective multicenter international cohort longitudinal pilot study of 548 subjects - Susca, Nicola; Solimando, Antonio Giovanni; Borrelli, Paola; Marziliano, Donatello; Monitillo, Francesco; Raimondo, Pasquale; Vestito, Domenico; Lopizzo, Agostino; Brindicci, Gaetano; Abumayyaleh, Mohammad S. A.; El-Battrawy, Ibrahim; Saracino, Annalisa; et al. (Journal of cardiovascular development and disease, 2023)
COVID-19 has threatened the capability of receiving and allocating patients in emergency departments (EDs) all over the world. This is a retrospective cohort study to explore the role of a simple procedure like an ECG to screen for the severity of COVID-19 on admission to the ED. For this study, 548 consecutive patients were enrolled in a multicenter international registry and stratified upon ECG on admission with a simple distinction between normal vs. abnormal rhythm. Among patients in the abnormal ECG group were those with heart rates higher than 100 beats per minute and/or atrial fibrillation. Survival in patients with normal ECG rhythm was deemed below 75% after 58 days and then stabilized, while survival in patients with abnormal ECG rhythm was deemed below 75% after 11 days and below 50% after 21 days. A multivariate analysis including abnormal rhythm, gender, age, diabetes, obesity, respiratory failure during hospitalization, heart failure during hospitalization, and abnormal rhythm was an independent predictor of death (HR 7.20 95% CI 3.63-14.28, p < 0.01). This finding, if confirmed in large prospective studies, is promising for identifying a cheap and simple procedure for patients in need of a closer look.